Childcare in the Central Region of Argentina: An Analysis of Gender and Socioeconomic Inequalities - Logiodice, Luisina (Sociedad y Economía, 2025)
This article aims to analyze child care home configuration in the central region of the country, based on the intersection of socioeconomic and gender inequalities. Some of the main results of a research carried out within the framework of a master’s thesis are presented and some decisions of the research process are recovered in a methodological-feminist reflexivity key. It is assumed a quantitative methodological approach, and data available from the National Survey of Social Structure were used. The work accounts for the primacy of two home models that have different forms of provision and generate disparate conditions of possibility to organize care. Likewise, the persistent maternalization of child care in the region and a tendency towards commodification in early childhood are recognized. In summary, divergent ways of caring for children are recognized based on the gender who leads the home, and therefore the type of provision they have, the socioeconomic level and the age of the children.